Integrating Intravascular Lithotripsy to Overcome Severe Aorto-Iliac Atherosclerosis in Standard Endovascular Aortic Repair: A Case Report - Giuseppe Mastropaolo; Andrea Cumino; Fabiana Zandrino; Sara Pomatto; Vittorio Pasta; Ilaria Ambrogio; Alberto Pecchio (EJVES Vascular Forum)
Introduction: Endovascular aneurysm repair (EVAR) is a safe and widespread treatment option for abdominal aortic aneurysm (AAA). Unfavourable anatomy, such as hostile neck and aorto-iliac atherosclerosis, can lead to many complications and compromise the long term reliability of the endograft, resulting in a high rate of EVAR failure. Intravascular lithotripsy (IVL) has emerged as an alternative treatment to address severe iliofemoral atherosclerosis, aiding trackability of devices in EVAR. However, the use of IVL to address severe calcification in hostile necks has not yet been described. Report: A 74 year old man with multiple comorbidities was referred for definitive treatment of an asymptomatic infrarenal AAA with severe aorto-iliac atherosclerosis. Kissing lithotripsy was firstly performed to treat the calcified stenosis of the aortic bifurcation and iliac axes. To prevent infolding and type Ia endoleak (ELIa), IVL was also performed through simultaneous inflation of two IVL balloon catheters and a compliant aortic balloon on a conical shape neck with an eccentric calcified plaque. The procedure was completed with standard EVAR. The three month follow up computed tomography angiography confirmed a successful outcome with shrinkage of the excluded aneurysmal sac, patent iliac axes, and complete disruption of the severe eccentric calcification of the aortic neck with no signs of infolding or endoleak. Discussion: This case report highlights the potential of IVL to improve the proximal sealing zone, prevent infolding and ELIa, enhance trackability of devices, reduce major complications, and extend the application of standard EVAR in patients with challenging anatomy. However, further studies and long term follow up are needed to define the efficacy and safety of integrating IVL in standard EVAR.